1976
DOI: 10.1007/bf00497681
|View full text |Cite
|
Sign up to set email alerts
|

The 18 p- syndrome

Abstract: Four children, two girls and two boys, were found to have a short arm deletion of chromosome No. 18. Three of them exhibit a typical dysmorphy of the face showing retraction of the midface, broad-based, flat nose, hypertelorism, epicanthus, "carp mouth", big, protruding, and low set ears, as well as a variable number of Turner-like features, failure of growth, mental retardation, and muscular hypotonia. A newly born child, who died at 2 days of age exhibited severe brain defects of holoprosencephalic series. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…The only congenital malformation of the brain found in present study was a hydrocephalus and a Dandy Walker malformation (Case 6). Postnatal growth retardation has been reported as almost a constant feature of the 18p deletion [Faust et al, 1976;Kanjilial et al, 1988], but found in only 4/7 of present study, and none of them was extremely short.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The only congenital malformation of the brain found in present study was a hydrocephalus and a Dandy Walker malformation (Case 6). Postnatal growth retardation has been reported as almost a constant feature of the 18p deletion [Faust et al, 1976;Kanjilial et al, 1988], but found in only 4/7 of present study, and none of them was extremely short.…”
Section: Discussionmentioning
confidence: 60%
“…The most specific features of present children were the ptosis and the slowness in motion and action [Faust et al, 1976;Thompson et al, 1986]. The ptosis was in three of present seven cases that severe that it had to be surgically corrected.…”
Section: Discussionmentioning
confidence: 86%
“…Of more than 80 cases with 18p - (Faust et al, 1976), at least 12 cases were the result of a translocation involving chromosome 18 and one of the acrocentric chromosomes. Almost half of these cases had a carrier parent, and the remainder were de novo cases (Lurie and Lazjuk, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic expression of 18pcases is variable: the common features are growth and mental deficiency, hypertelorism, epicanthic folds, and large, protruding, and low set ears (Faust et al, 1976). The association of arhinencephaly and cebocephaly with 1 8p -is also known (Lurie and Lazjuk, 1972).…”
mentioning
confidence: 99%
“…Short stature and dental decay are common. Other skeletal, cardiac, renal, and fundal abnormalities have also been described [Faust et al, 1976;Schinzel et al, 1974;Pearl, 1989;Movahhedian et al, 1991;Anderson-Shotwell and Wilson, 19891. On the other hand, deletions of the long arm of chromosome 3 are extremely rare.…”
Section: Introductionmentioning
confidence: 87%